Nurse-led adult ENT pre-operative assessment. - Bhutta, M; Boutchier, B; Latif, M (2008)
Pre-operative assessment in some ENT departments is now nurse-led rather than doctor-led. Appropriately trained nursing staff can perform medical aspects of pre-operative assessment to the same or a better standard than a doctor. Almost all patients are satisfied with a nurse-led pre-operative assessment, and in some cases they prefer it.